Synthesis, Crystal Structure, Characterization, and Hydrophobicity Tests of Bismuth(III)– and Silver(I)–Triammionium Bromide Low-Dimensional Perovskites - Victor C. Sousa; Bruno Dival; Willian X. C. Oliveira (Compounds, 2025)
This work describes the synthesis, crystal structure, and hydrophobicity tests of four bismuth(III)– and silver(I)–bromide complexes using the triammonium cations diethylenetriaminonium (H3DETA3+) and N,N,N′,N″,N‴-pentamethyldiethylenetriammonium (H3PMDTA3+). The prepared compounds are the 0D perovskites (H3DETA)[BiBr6] (1), (H3DETA)2[AgBr4]Br3 (2), and (H3PMDTA)[BiBr6] (3), as well as the 1D/2D mixed perovskite with minimum formula (H3PMDTA)[Ag3Br6] (4), being the last three novel materials. Compounds 1 and 3 crystallize in the orthorhombic P212121 space group and are discrete [BiBr6]3− units with the cation surrounding them. In both compounds, the bismuth(III) metal ion is found in a distorted octahedral coordination geometry. Compound 2 crystallizes in the monoclinic P21/c space group, and it is a mixed salt consisting of (H3DETA)[AgBr4] and (H3DETA)Br3, whereas the silver(I) complexes are also isolated. Finally, compound 4, which crystallizes in the orthorhombic space group Pbcn, is a combination of a 2D and 1D silver–bromide perovskite, with the cations filling the voids. The 2D structure has the minimal formula [Ag4Br7]3−, with the 1D coordination polymer [Ag2Br5]3− being both built up by a combination of bromide ions acting as tetrahedra corner and edge-sharing bridging ligands. The silver(I) in 2 and 4 is found in a tetrahedral coordination geometry. All compounds were deposited on pristine FTO glass, resulting in an increase in the contact angle from 22° to 44°, 36°, 62°, and 54° for films of 1, 2, 3, and 4, respectively. Compounds 1 and 3 were also deposited onto Cs2AgBiBr6 film, and the contact angles were observed to be the same as when deposited directly onto the FTO cover glass.